Basic Sentence Analysis of Subject Verb and Complement Pattern Found in 21st Album by Adele - Ni Kadek Sari; Putu Devi Maharani; I G. B. Wahyu Nugraha Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
AbstractThere are many patterns used in song lyrics. This patterns support each other to make the song deeply meaningful when the listener listen the song. This study is about the basic sentence of S-V-C pattern found in Adele Album Song Lyrics especially in 21st Album. It aims to find out the types of basic sentence patterns and the most occurring type of basic sentence pattern which found in this song lyrics. Based on the theory from Quirk et al (1973) and supported with the theory from Brown and Miller (1991). The study found that subject and verb, subject verb and complement, subject verb and adverbial, subject verb and object, subject verb object and complement, subject verb object and adverbial, and subject verb object and object found in this song lyrics. The result of this study are total 63 lyrics found as the data. And it shows that found 9 basic sentence (14%) of S-V pattern, 16 basic sentence (25%) of S-V-C pattern, 13 basic sentence (21%) of S-V-A pattern, 13 basic sentence (21%) of S-V-O pattern, 4 basic sentence (6%) of S-V-O-C pattern, 7 basic sentence (11%) of S-V-O-A pattern, 1 basic sentence (2%) of S-V-O-O pattern. Keywords: basic sentence patterns, Adele’s song, types